Make it mean! Using a ‘community of inquiry’ to improve language skills in the ESL classroom - Preece, Abdul Shakour Duncan (2013)
The purpose of the study was to explore ways of making ESL classes more engaging for language learners at the International Islamic University Malaysia (IIUM). To this end, an instructional method known as ‘Community of Inquiry' (CI) where students sit in a circle and explain, challenge and justify one another’s opinions, arguments and assertions was combined with specially written ‘thinking stories' containing philosophical issues and elements of relevance to learners' culture. Two such stories were written and taught to a class of intermediate level, ESL learners at IIUM, over a five-week period, using CI method.